THE POSITION OF INTANGIBLE CULTURAL HERITAGE ELEMENTS (SOKUM) IN TOURISM STUDENTS’ LEISURE TIME ACTIVITIES (Third Sector Social Economic Review, 2019)
The aim of this study is to determine the awareness-experience-willingness levels of tourism students towards the elements of SOKUM, which has become a touristic product within the leisure activities. It also tries to determine whether there is a difference between associate-undergraduate-postgraduate degrees of tourism students in this area, and suggestions have been made to increase awareness and participation in activities related to SOKUM elements. Nevsehir Haci Bektas Veli University is in Cappadocia, a World Heritage area and most important cultural tourism destination of Turkey. For this reason, the population of the study consists of approximately 2000 students who majors tourism at different levels at this university. In order to reach the number of samples that can be generalized to the universe, 560 questionnaires are distributed by random sampling method and 496 questionnaires are analyzed. A questionnaire is prepared by examining the studies that measure the awareness and leisure time habits of young people against SOKUM elements. The averages are taken to determine the awareness-experience-willingness levels of the participants. In order to determine the differences between the students in different educational levels, T-test and ANOVA analysis is used. The SOKUM elements which they have most well-known are Karagoz-Hacivat, folk dances, and folk music activities. The SOKUM elements which they have most experiences are folk dances, folk music activities, and pottery. The SOKUM elements which they have most willing to participate are marbling art, folk dances, and folk music activities.
Keywords: SOKUM; Tourism; Leisure Activities; University Students; Touristic Product